Role and interactions of organelle stress in septic cardiomyopathy - Wei Wei; Zhang Jinbo; Zhang Zhaocai (生物医学转化)
Septic cardiomyopathy (SCM) refers to the cardiac dysfunction induced by sepsis, a longstanding focus in clinical research. It usually presents as reversible myocardial dysfunction with a complex pathogenesis. The excessive inflammatory response, immune dysfunction, and dysregulation of homeostasis induced by sepsis can trigger abnormal stress responses in organelles such as endoplasmic reticulum, mitochondria, and Golgi apparatus, regulating the pathophysiological progression of SCM. This article focuses on organelle stress responses, analyzing their roles and mechanisms in SCM. In addition, we further discuss the interactions between different organelle stress responses in the disease progression, providing a valuable reference for advancing the understanding of SCM and developing corresponding therapeutic strategies.